From Compliance to Learning: Citizen Feedback in Indonesian Public Service - Agung Febri Wibowo S; Muhammad Ngafifi (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2025)
Citizen satisfaction surveys are widely implemented in public service organisations, yet their contribution to service improvement often remains limited when feedback is treated primarily as a compliance requirement. This study examines how satisfaction survey results are utilised for service improvement by focusing on the organisational processes through which feedback is interpreted and acted upon. Using a mixed-methods analytical case study of the State Asset and Auction Service Office (Kantor Pelayanan Kekayaan Negara dan Lelang – KPKNL) Palu, the study draws on official satisfaction survey data collected in 2023, complemented by internal discussions and documentary analysis. The findings show that satisfaction surveys contribute to organisational change only when feedback is embedded within routine managerial and coordination processes. Rather than generating automatic responsiveness, feedback utilisation unfolds through four interconnected stages: shared awareness of service problems, routinised coordination within internal forums, selective material change in feasible service areas, and outcomes that remain structurally bounded by organisational constraints. Improvements were more readily achieved in tangible and informational aspects of service delivery, while structurally complex issues such as service timeliness proved less responsive to short-term intervention. By foregrounding organisational routines and constraints, this study advances a process-oriented understanding of feedback-driven organisational learning in public service organisations. The findings highlight the importance of shifting attention from the collection of satisfaction data toward the institutionalisation of feedback utilisation as a foundation for incremental, learning-oriented service improvement.